Sistema integrado de registros electrónicos y su relación con la mejora de procesos contables tradicionales en colaboradores de estudios contables Iquitos año 2024 - Alvan Yalta, Joseph Isaias (2024)
Companies today face challenges to optimize their accounting processes, in this sense the tax administration has implemented the Integrated Electronic Records System (SIRE), which estimates will improve traditional accounting processes, currently not many studies have been carried out on how accounting firm collaborators perceive its implementation, the study set as a general objective to determine the relationship between the integrated electronic records system and the improvement of traditional accounting processes in accounting firm collaborators Iquitos year 2023, for this a quantitative approach was developed, of a non-experimental correlational type, with the use of a 20-item questionnaire, with a statistical reliability of 0.955, the analysis of results shows that there is a statistical correlation between the SIRE and the improvement of traditional accounting processes in the same way, a significant and positive relationship is identified with the improvement in information security, with the improvement of process efficiency and with the improvement of the presentation of tax information, it is also identified that more than 50% of respondents states that the system improves accounting management, and more than 60% value its contribution to efficiency and security, highlighting its importance in improving operational performance and protecting information.